Biodeteriogenne grzyby w kopalniach węgla kamiennego = Biodeteriogenic moulds in coal mines - Piontek, Marlena; Bednar, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Studies on the prevalence of fungi, including moulds in the mines are done for many years. Moulds and other biodeteriogenic organisms develop on any type of material used in excavations, because the damage caused by these are not inevitable. In coal mines the growth of microorganism favour mico-limate of the mine, specific environmental conditions, both high relative humidity and temperature.
Keywords: organizmy biodeteriogenne; grzyby pleśniowe; kopalnie węgla kamiennego; biodeteriogenic organisms; moulds; coal mines